Parent‐infant Psychotherapy for Improving Parental and Infant Mental Health: A Systematic Review. Issue 1 (2nd March 2015) - Barlow, Jane; Bennett, Cathy; Midgley, Nick; Larkin, Soili K.; Wei, Yinghui
Abstract : This co‐registered Cochrane and Campbell systematic review compares the effectiveness of parent‐infant psychotherapy (PIP) in improving the mental health of parents, the parent‐infant relationship and infant emotional wellbeing with that of no treatment, treatment as usual and alternative treatments. The review summarises findings from eight randomised controlled trials (RCTs), with a total of 846 participants. Compared with no treatment or treatment‐as‐usual, PIP participants show an increase in the number of infants securely attached; fewer infants with an avoidant or disorganised attachment style; and more infants moving from insecure to secure attachment. This was maintained at follow up. PIP is neither more nor less effective than no treatment or treatment‐as‐usual in improving maternal mental health, and reflective functioning; infant stress and development; or the quality of the mother‐infant interaction. Parent‐infant psychotherapy (PIP) is a dyadic intervention that works with parent and infant together, with the aim of improving the parent‐infant relationship and promoting infant attachment and optimal infant development. PIP aims to achieve this by targeting the mother's view of her infant, which may be affected by her own experiences, and linking them to her current relationship to her child, in order to improve the parent‐infant relationship directly. Abstract: BACKGROUND: Parent‐infant psychotherapy (PIP) is a dyadic intervention that works with parent and infant together, with the aim of improving the parent‐infant relationship and promoting infant attachment and optimal infant development. PIP aims to achieve this by targeting the mother's view of her infant, which may be affected by her own experiences, and linking them to her current relationship to her child, in order to improve the parent‐infant relationship directly. OBJECTIVES: To assess the effectiveness of PIP in improving parental and infant mental health and the parent‐infant relationship. To identify the programme components that appear to be associated with more effective outcomes and factors that modify intervention effectiveness (e.g. programme duration, programme focus). SEARCH METHODS: We searched the following electronic databases on 13 January 2014: Cochrane Central Register of Controlled Trials (CENTRAL, 2014, Issue 1), Ovid MEDLINE, EMBASE, CINAHL, PsycINFO, BIOSIS Citation Index, Science Citation Index, ERIC, and Sociological Abstracts. We also searched the meta Register of Controlled Trials, checked reference lists, and contacted study authors and other experts. SELECTION CRITERIA: Two review authors assessed study eligibility independently. We included randomised controlled trials (RCT) and quasi‐randomised controlled trials (quasi‐RCT) that compared a PIP programme directed at parents with infants aged 24 months or less at study entry, with a control condition (i.e. waiting‐list, no treatment or treatment‐as‐usual), and used at least one standardised measure of parental or infant functioning. We also included studies that only used a second treatment group. DATA COLLECTION AND ANALYSIS: We adhered to the standard methodological procedures of The Cochrane Collaboration. We standardised the treatment effect for each outcome in each study by dividing the mean difference (MD) in post‐intervention scores between the intervention and control groups by the pooled standard deviation. We presented standardised mean differences (SMDs) and 95% confidence intervals (CI) for continuous data, and risk ratios (RR) for dichotomous data. We undertook meta‐analysis using a random‐effects model. MAIN RESULTS: We included eight studies comprising 846 randomised participants, of which four studies involved comparisons of PIP with control groups only. Four studies involved comparisons with another treatment group (i.e. another PIP, video‐interaction guidance, psychoeducation, counselling or cognitive behavioural therapy (CBT)), two of these studies included a control group in addition to an alternative treatment group. Samples included women with postpartum depression, anxious or insecure attachment, maltreated, and prison populations. We assessed potential bias (random sequence generation, allocation concealment, incomplete outcome data, selective reporting, blinding of participants and personnel, blinding of outcome assessment, and other bias). Four studies were at low risk of bias in four or more domains. Four studies were at high risk of bias for allocation concealment, and no study blinded participants or personnel to the intervention. Five studies did not provide adequate information for assessment of risk of bias in at least one domain (rated as unclear). Six studies contributed data to the PIP versus control comparisons producing 19 meta‐analyses of outcomes measured at post‐intervention or follow‐up, or both, for the primary outcomes of parental depression (both dichotomous and continuous data); measures of parent‐child interaction (i.e. maternal sensitivity, child involvement and parent engagement; infant attachment category (secure, avoidant, disorganised, resistant); attachment change (insecure to secure, stable secure, secure to insecure, stable insecure); infant behaviour and secondary outcomes (e.g. infant cognitive development). The results favoured neither PIP nor control for incidence of parental depression (RR 0.74, 95% CI 0.52 to 1.04, 3 studies, 278 participants, low quality evidence) or parent‐reported levels of depression (SMD ‐ 0.22, 95% CI ‐0.46 to 0.02, 4 studies, 356 participants, low quality evidence). There were improvements favouring PIP in the proportion of infants securely attached at post‐intervention (RR 8.93, 95% CI 1.25 to 63.70, 2 studies, 168 participants, very low quality evidence); a reduction in the number of infants with an avoidant attachment style at post‐intervention (RR 0.48, 95% CI 0.24 to 0.95, 2 studies, 168 participants, low quality evidence); fewer infants with disorganised attachment at post‐intervention (RR 0.32, 95% CI 0.17 to 0.58, 2 studies, 168 participants, low quality evidence); and an increase in the proportion of infants moving from insecure to secure attachment at post‐intervention (RR 11.45, 95% CI 3.11 to 42.08, 2 studies, 168 participants, low quality evidence). There were no differences between PIP and control in any of the meta‐analyses for the remaining primary outcomes (i.e. adverse effects), or secondary outcomes. Four studies contributed data at post‐intervention or follow‐up to the PIP versus alternative treatment analyses producing 15 meta‐analyses measuring parent mental health (depression); parent‐infant interaction (maternal sensitivity); infant attachment category (secure, avoidant, resistant, disorganised) and attachment change (insecure to secure, stable secure, secure to insecure, stable insecure); infant behaviour and infant cognitive development. None of the remaining meta‐analyses of PIP versus alternative treatment for primary outcomes (i.e. adverse effects), or secondary outcomes showed differences in outcome or any adverse changes. We used the Grades of Recommendation, Assessment, Development and Evaluation Working Group (GRADE) approach to rate the overall quality of the evidence. For all comparisons, we rated the evidence as low or very low quality for parental depression and secure or disorganised infant attachment. Where we downgraded the evidence, it was because there was risk of bias in the study design or execution of the trial. The included studies also involved relatively few participants and wide CI values (imprecision), and, in some cases, we detected clinical and statistical heterogeneity (inconsistency). Lower quality evidence resulted in lower confidence in the estimate of effect for those outcomes. AUTHORS' CONCLUSIONS: Although the findings of the current review suggest that PIP is a promising model in terms of improving infant attachment security in high‐risk families, there were no significant differences compared with no treatment or treatment‐as‐usual for other parent‐based or relationship‐based outcomes, and no evidence that PIP is more effective than other methods of working with parents and infants. Further rigorous research is needed to establish the impact of PIP on potentially important mediating factors such as parental mental health, reflective functioning, and parent‐infant interaction. Plain language summary: PARENT‐INFANT PSYCHOTHERAPY FOR IMPROVING PARENT AND INFANT WELL‐BEING: Background: Parent‐infant psychotherapy (PIP) is intended to address problems in the parent‐infant relationship, and problems such as excessive crying and sleeping/eating difficulties. A parent‐infant psychotherapist works directly with the parent and infant in the home or clinic, to identify unconscious patterns of relating and behaving, and influences from the past that are impeding the parent‐infant relationship. Parents may be referred to this service (e.g. by a general practitioner in the UK) or may self refer to privately run services. The intervention is delivered to individual dyads but can also be delivered to small groups of parents and infants. Review question: This review examined whether PIP is effective in improving the parent‐infant relationship, or other aspects of parent or infant functioning, and to identify the programme components that appear to be associated with more effective outcomes and factors that modify intervention effectiveness (e.g. programme duration, programme focus). Study characteristics: We searched electronic databases and identified randomised controlled trials (RCTs, where participants are randomly allocated to one of two or more treatment groups) and one cluster randomised trial (where prisons rather than participants were used as the unit of randomisation), in which participants had been allocated to a receive PIP versus a control group, and which reported results using at least one standard measure of outcome (i.e. an instrument which has been tested to ensure that it reliably measures the outcome under investigation). Evidence is current to 13 January 2014. We identified eight studies with 846 randomised participants comparing either PIP with a no‐treatment control group (four studies) or comparing PIP with other types of treatment (four studies). Key results: The studies comparing PIP with a no‐treatment control group contributed data to 19 meta‐analyses of the primary outcomes of parental mental health (depression), parent‐infant interaction outcomes of maternal sensitivity (i.e. the extent to which the caregiver responds in a timely and attuned manner), child involvement and parent positive engagement, and infant outcomes of infant attachment category (the infant's ability to seek and maintain closeness to primary caregiver ‐ infant attachment is classified as follows: 'secure' infant attachment is a positive outcome, which indicates that the infant is able to be comforted when distressed and is able to use the parent as a secure base from which to explore the environment. Infants who are insecurely attached are either 'avoidant' (i.e. appear not to need comforting when they are distressed and attempt to manage the distress themselves); or 'resistant' (i.e. unable to be comforted when distressed and alternate between resistance and anger). Children who are defined as 'disorganised' are unable to produce a coherent strategy in the face of distress and produce behaviour that is a mixture of approach and avoidance to the caregiver); and the secondary outcomes of infant behaviour and infant cognitive development (i.e. intellectual development, including thinking, problem solving and communicating). In our analyses, parents who received PIP were more likely to have an infant who was securely emotionally attached to the parent after the intervention; this a favourable outcome but there is very low quality evidence to support it. The studies comparing PIP with another model of treatment contributed data to 15 meta‐analysis assessments of primary outcomes, including parental mental health, parent‐infant interaction (maternal sensitivity); infant attachment and infant behaviour, or secondary infant outcomes such as infant cognitive development. None of these comparisons showed differences that favoured either PIP or the alternative intervention. None of the comparisons of PIP with either a control or comparison treatment group showed adverse changes for any outcome. We conclude that although PIP appears to be a promising method of improving infant attachment security, there is no evidence about its benefits in terms of other outcomes, and no evidence to show that it is more effective than other types of treatment for parents and infants. Further research is needed. Quality of the evidence: The included studies were unclear about important quality criteria, had limitations in terms of their design or methods, or we judged that there was risk of bias in the trial. This lower quality evidence gives us less confidence in the observed effects.